2017
DOI: 10.18671/scifor.v45n114.10
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de Trichoderma spp. no crescimento de mudas clonais de Eucalyptus camaldulensis

Abstract: Fungos do gênero Trichoderma são largamente utilizados no biocontrole de fitopatógenos, além de serem capazes de estabelecer associações com plantas, aumentando seu potencial de desenvolvimento. Este trabalho avaliou o desenvolvimento e qualidade de mudas clonais de Eucalyptus camaldulensis (clone 58) inoculadas com duas espécies de Trichoderma: T. harzianum e T. virens, por diferentes métodos, a saber: tratamento das miniestacas; incorporação de grãos de arroz colonizados ao substrato; pulverização de suspens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 23 publications
2
15
0
3
Order By: Relevance
“…Thus, it has become extremely important for this work to evaluate endophytic colonization. There are many studies that have been reporting Trichoderma colonizing the roots of eucalyptus (Sbravatti Junior et al, 2013, Azevedo et al, 2017. In the present study, the CEN262 strain showed the best growth of eucalyptus plants in seedlings experiment (Table 5), and positive results of endophytic colonization of eucalyptus roots.…”
Section: Discussionsupporting
confidence: 64%
“…Thus, it has become extremely important for this work to evaluate endophytic colonization. There are many studies that have been reporting Trichoderma colonizing the roots of eucalyptus (Sbravatti Junior et al, 2013, Azevedo et al, 2017. In the present study, the CEN262 strain showed the best growth of eucalyptus plants in seedlings experiment (Table 5), and positive results of endophytic colonization of eucalyptus roots.…”
Section: Discussionsupporting
confidence: 64%
“…Different results from those found for the six analyzed variables in the K. ivorensis seedlings subjected to biological treatment, where an influence only on height and number of leaflets occured, were obtained by Azevedo et al (2017), when evaluating the effect of vermicompost and/or Trichoderma isolates as growth promoters for Jacaranda micrantha Cham seedlings. (Caroba).…”
Section: Discussionmentioning
confidence: 62%
“…Trichoderma virens e Trichoderma harzianum apresentam eficiência como promotores de crescimento de mudas clonais de Eucalyptus camaldulensis em condições de viveiro (Azevedo et al, 2017). Segundo os autores o tratamento das minestacas, pela imersão da base em pó de arroz colonizado com Trichoderma virens, mostra ser o tratamento mais eficiente na promoção do desenvolvimento e qualidade das mudas de eucalipto.…”
Section: Isoladosunclassified
“…Atualmente micro-organismos como bactérias e fungos são mais utilizados para otimizar as produções agrícolas e silviculturais, combatendo fitopatógenos, solubilizando nutrientes e sintetizando hormônios de crescimento. Um desses micro-organismos capazes de propiciar essa gama de benefícios são os fungos pertencentes ao gênero Trichoderma (Hermosa et al, 2013;Azevedo et al, 2017;Druzhinina et al, 2018;Meyer et al, 2019).…”
Section: Introductionunclassified